2006
DOI: 10.1371/journal.ppat.0020105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Expression of Human Cell Division Autoantigen-1 Influence Toxoplasma gondii Growth and Development

Abstract: Toxoplasma is a significant opportunistic pathogen in AIDS, and bradyzoite differentiation is the critical step in the pathogenesis of chronic infection. Bradyzoite development has an apparent tropism for cells and tissues of the central nervous system, suggesting the need for a specific molecular environment in the host cell, but it is unknown whether this environment is parasite directed or the result of molecular features specific to the host cell itself. We have determined that a trisubstituted pyrrole act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 53 publications
5
118
0
1
Order By: Relevance
“…First, we reasoned that if SAL and GA function through the host cells, treatment with either drug prior to infection may affect parasite replication. Such effects of drug preconditioning were reported by Radke et al, who demonstrated that pretreatment of HFF host cells with compound 1 (a trisubstituted pyrrole and bradyzoite inducer) prior to infection with tachyzoites reduced parasite proliferation by promoting bradyzoite formation (18). We therefore pretreated HFF monolayers with increasing concentrations of SAL, GA, or vehicle for 24 h prior to infection and then counted the number of parasites per vacuole 24 h postinfection.…”
Section: Fig 3 Sal and Ga Impede Reactivation Of Latent Bradyzoites Imentioning
confidence: 63%
“…First, we reasoned that if SAL and GA function through the host cells, treatment with either drug prior to infection may affect parasite replication. Such effects of drug preconditioning were reported by Radke et al, who demonstrated that pretreatment of HFF host cells with compound 1 (a trisubstituted pyrrole and bradyzoite inducer) prior to infection with tachyzoites reduced parasite proliferation by promoting bradyzoite formation (18). We therefore pretreated HFF monolayers with increasing concentrations of SAL, GA, or vehicle for 24 h prior to infection and then counted the number of parasites per vacuole 24 h postinfection.…”
Section: Fig 3 Sal and Ga Impede Reactivation Of Latent Bradyzoites Imentioning
confidence: 63%
“…We have recently obtained evidence that T. gondii infection promotes the G 1 -to-S transition in infected HFFs (R. E. Molestina, E. I. Guendy, and A. P. Sinai, unpublished data). Toxoplasma infection does not promote the replication of the infected cell, unlike the related Apicomplexa of Theileria species (22), but clearly is influenced by cell cycle modulators, as seen with the overexpression of the CDA1 gene promoting cystogenesis (71). …”
Section: Vol 76 2008 Modulation Of the Host Cell Proteome By T Gonmentioning
confidence: 99%
“…TSPY is homologous to SET/NAP proteins, which play a role in nucleosome assembly and chromatin remodelling (Wagner et al, 2006). Next to some pseudogenes, also a functional X chromosomal homolog of TSPY exists in humans (called TSPYlike 2 or TSPX, DENTT, hCINAP, CDA1, se20-4), which, in contrast to TSPY, is widely expressed and plays a role in growth arrest, TGFbeta1 signalling and regulates growth and differentiation of the intracellular parasite toxoplasma gondii (Chai et al, 2001;Ozbun et al, 2005;Radke et al, 2006).…”
Section: Oct3/4 Biology and Diagnostic Markermentioning
confidence: 99%